Economic Development and Environmental Protection - Marzio Galeotti (Fondazione Eni Enrico Mattei (FEEM), 2003)
There is a long-standing debate on the relationship between economic development and environmental quality. From a sustainable development viewpoint there has been a growing concern that the economic expansion of the world economy will cause irreparable damage to our planet. In the last few years several studies have appeared dealing with the relationship between the scale of economic activity and the level of pollution. In particular, if we concentrate on local pollutants several empirical studies have identified a bell shaped curve linking pollution to per capita GDP (in the case of global pollutants like CO2 the evidence is less clear-cut). This behaviour implies that, starting from low per capita income levels, per capita emissions or concentrations tend to increase but at a slower pace. After a certain level of income (which typically differs across pollutants) the turning point pollution starts to decline as income further increases. In analogy with the historic relationship between income distribution and income growth, the inverted-U relationship between per capita income and pollution has been termed Environmental Kuznets Curve. The purpose of this chapter is not to provide an overview the literature: there are several survey papers around doing precisely that. We instead reconsider the explanations that have been put forth for its inverted-U pattern. We look at the literature from this perspective. In addition, without resorting to any econometric estimation, we consider whether simple data analysis can help to shed some light on the motives that can rationalize the Environmental Kuznets Curve.
Keywords: H0; H2; H3; 330; Climate Policy; Environmental Modeling; Integrated Assessment; Technical Change; Umweltbelastung; Entwicklung; Umweltschutz; Technischer Fortschritt; Welt; Environmental Kuznets Curve